Evaluating the potential of cybercartography in facilitating Indigenous self-determination: a First Nations case study on Vancouver Island - Robson, Dexter (2020)
Since the arrival of settlers in the 16th century, the Canadian Government has dispossessed First Nations people of their land and culture through a history of colonialism. This has led to over a century of contentious relationships between First Nations and the Canadian Government in which First Nations have often struggled with the revitalization and reclamation of their culture and land due to oppressive systemic structures. Cartography has been one approach, among many, adopted by First Nations to facilitate self-determination in recent decades. However, the role of cartography has been one focused on western technocratic approaches of drawing territorial boundaries as part of the land claims process. Such approaches may assist First Nations in documenting land use and negotiating territorial rights and as such move them towards self-determination. Conventional western cartography is inherently incapable of representing the rich spatial nature of First Nations’ sense of cultural place. More recently, cybercartography has emerged due to technological advances in software and web-based publishing that has the potential to encapsulate First Nations’ oral history and culture by providing digital multimedia elements (i.e. audio, imagery, and video) within a digital spatial context. The use of cybercartography in this manner is quickly increasing over time, but research is lacking in understanding how new representations of First Nations history and culture through cybercartographic frameworks explicitly facilitate, or prohibit, First Nations ability to attain self-determination. To address this gap, this study evaluates the ways in which contemporary cybercartographic technologies may facilitate the process of self-determination through an application development and interview process with a local First Nation on Vancouver island, BC. The research process throughout the project are evaluated using the Indigenous principles of Ownership, Control, Access, and Possession (OCAP) and uses this as a framework to ...